2021
DOI: 10.1111/1365-2664.13934
|View full text |Cite
|
Sign up to set email alerts
|

Plant regulatory lists in the United States are reactive and inconsistent

Abstract: 1. Global invasive species introductions are rising, necessitating coordinated regulatory strategies within and across national borders. Although states and nations address their unique priorities using plant regulations, these regulations are most likely to reduce invasive plant introduction and spread if they are consistently enacted across political borders and proactively restrict spread early in the invasion process. Further, a unified regulatory landscape is particularly important given the imminent rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…As a result, northeast states should agree about which plants are high risk, ideally leading to similar regulatory lists. Unfortunately, inconsistent regulatory lists are common internationally (Courchamp et al, 2017;Early et al, 2016) and across US states (Beaury, Fusco, et al, 2021;Lakoba et al, 2020). For example, Buerger et al (2016) evaluated regulated species in six Midwestern states and found only 14 species F I G U R E 4 Risk assessment scores for 52 terrestrial invasive plants evaluated by both New Hampshire (NH) and New York (NY) showed a weak positive correlation (R 2 = 0.179).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, northeast states should agree about which plants are high risk, ideally leading to similar regulatory lists. Unfortunately, inconsistent regulatory lists are common internationally (Courchamp et al, 2017;Early et al, 2016) and across US states (Beaury, Fusco, et al, 2021;Lakoba et al, 2020). For example, Buerger et al (2016) evaluated regulated species in six Midwestern states and found only 14 species F I G U R E 4 Risk assessment scores for 52 terrestrial invasive plants evaluated by both New Hampshire (NH) and New York (NY) showed a weak positive correlation (R 2 = 0.179).…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded five species ( Sagittaria japonica , Typha gracilis , Typha laxmannii , and Typha minima listed in NH, and the hybrid Myriophyllum heterophyllum × Myriophyllum laxum listed in NY) whose scientific names were not listed in the USDA PLANTS database (USDA PLANTS, 2021). Following Beaury, Fusco, et al (2021), we measured consistency between states by aggregating all regulated species into a single “regional list” and we calculated the percentage of this regional list that was regulated within each state. Also following Beaury, Fusco, et al (2021), we calculated the proportion of counties within the state where each regulated species was present as a metric of proactivity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations